2017
DOI: 10.1089/ars.2016.6900
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Metastable Regions and Their Connectivity in the Inactivation of a Redox-Regulated Chaperone and Its Inter-Chaperone Crosstalk

Abstract: By modifying the Hsp33's sequence, we reveal that the metastable region has evolved to abolish redox-dependent chaperone activity, rather than enhance binding affinity for client proteins. The intrinsically disordered region of Hsp33 serves as an anchor for the reduced, inactive state of Hsp33, and it dramatically affects the crosstalk with the synergetic chaperone system, DnaK/J. Using mass spectrometry, we describe the role that the metastable region plays in determining client specificity during normal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…In fact, in addition to CALR, several studies have indicated that numerous protein and RNA chaperones are either disordered or contain intrinsically disordered regions needed for their functionality (Tompa and Csermely, 2004 ; Tompa and Kovacs, 2010 ; Kovacs and Tompa, 2012 ). These proteins include late embryogenesis abundant (LEA) and other stress-related plant proteins (Kovacs et al, 2008a , b ; Cuevas-Velazquez et al, 2017 ), human chaperones engaged in neurodegenerative diseases (Uversky, 2011 ), histone chaperones (Liu et al, 2017 ; Warren and Shechter, 2017 ), a redox-regulated chaperone Hsp33 (Rimon et al, 2017 ), small heat shock proteins (Sudnitsyna et al, 2012 ), and the heat shock transcription factors (Westerheide et al, 2012 ).…”
Section: Structural Features Of Normal Human Calrmentioning
confidence: 99%
“…In fact, in addition to CALR, several studies have indicated that numerous protein and RNA chaperones are either disordered or contain intrinsically disordered regions needed for their functionality (Tompa and Csermely, 2004 ; Tompa and Kovacs, 2010 ; Kovacs and Tompa, 2012 ). These proteins include late embryogenesis abundant (LEA) and other stress-related plant proteins (Kovacs et al, 2008a , b ; Cuevas-Velazquez et al, 2017 ), human chaperones engaged in neurodegenerative diseases (Uversky, 2011 ), histone chaperones (Liu et al, 2017 ; Warren and Shechter, 2017 ), a redox-regulated chaperone Hsp33 (Rimon et al, 2017 ), small heat shock proteins (Sudnitsyna et al, 2012 ), and the heat shock transcription factors (Westerheide et al, 2012 ).…”
Section: Structural Features Of Normal Human Calrmentioning
confidence: 99%
“…Interestingly, the C-terminal domains of the two homologs show low sequence identity of 25%. However, both contain four conserved cysteine residues, oxidation of which leads to the partial unfolding of Hsp33 and exposure of hydrophobic regions crucial for the anti-aggregation activity (Ilbert et al, 2007;Rimon et al, 2017).…”
Section: Designing Chimeric Proteins To Investigate the Redox Regulatmentioning
confidence: 99%
“…This "perfect match" of the bacterial and TrypOx domains is very unique, as bacterial Hsp33 is a highly dynamic protein, mutation of which leads to either no or constitutive activity. Therefore, wild type-like redox-regulated chaperone and transfer activity can be obtained only by correct interactions between C-terminal, linker, and N-terminal domains (Rimon et al, 2017).…”
Section: The Hsp33 Homolog In Trypanosoma Brucei Trypox Is An Impormentioning
confidence: 99%
See 1 more Smart Citation
“…It was established that both accumulation of reactive oxygen species and protein misfolding are hallmarks of numerous neurological diseases and aging, thus tying these processes together. Recent studies in our and other labs have reported the discovery of a subgroup of proteinsredox switchesthat use thiol oxidation to mediate diverse physiological functions, including protein quality control 26,27,60 , merging redox and protein homeostasis together.…”
Section: Cdc48 Is a Link Between Redox And Protein Homeostasismentioning
confidence: 99%